The Impact of Climate Change on Vulnerable Populations Social Responses to a Changing Environment - Joseph, Debra D.; Doon, Roshnie A. (2023)
Climate change and urban development threaten health, undermine coping and deepen existing social and environmental inequities. A changing global environment requires transformative social responses: new partnerships, deep engagement with local communities, and innovations to strengthen individual and collective assets. The chapters of this proposed edited volume will be contributed mainly by established and emerging scholars from individuals, representing social work, sociology, development studies, law, government, social anthropology, urbanism, The chapters of this proposed edited volume will be contributed mainly by established and emerging scholars from individuals representing social work, sociology, development studies, public policy, and other social sciences This book is to be used for academics, policy makers, social work students, lecturers and other stakeholders to promote advocacy for vulnerable client groups affected by Climate Change. It gives some measure of hope and make the invisible visible to change.